SOIL AND WATER LOSSES FROM EXOTIC - TREE PLANTATIONS TREATED WITH NARROW TERRACES ON STEEP TERRAIN OF DOI ANGKHANG HIGHLAND PROJECT, CHIANG MAI - Tang, Nipon; Janmahasatien, Ruang; Maknual, Chatree (วารสารวนศาสตร์ไทย, 2022)
Soil and water losses from 6 exotic-tree species from Taiwan namely: Aleurites montana, Zalkova formosana, Liquidambar formosana, Acacia confusa, Fraxinus griffithii, and Paulonia taiwaniana planted on 2.0 x 2.5 m spacing of narrow bench terraces at Doi Angkhang, Amphoe Fang, Chiang Mai were investigated when the plantations aged at 2, 3 and 7 - year old. A single runoff plot of 4 x 15 sq. m was installed for each species and storm runoff and sediment were monitored in 1983, 1984 and 1988. Two additional plots were established in 1984 aiming to determine soil erodibility (K-value) in the Universal Soil Loss Equation (USLE) and to compare soil and water losses as well as efficiency of tree species and terracing in controling soil erosion (CP-factor in USLE) and surface flow, One out of two was non-terraced while another maintained in continuous fallow, periodically tilled up and down hill as a conventional corn seedbed condition and kept free from vegetation. Results indicated that at 2-yr old, soil and water losses from the first 5 species plots were averaged at 0.2 ton / ha and 17.1 mm respectively. The losses were reduced to 0.095 tons / ha and 13.5 mm respectively at 3-yr old plantation with insignificant differences among species but highly significance between the five species and the later two plots. The average amounts of soil loss from non-terraced reforestation and conventional fallow plots were found to be about 65 and 6,600 times greater than those of the terraced plantation plots while about 4.5 and 12 times were found for water loss. When the plantation was at 7-year old, soil loss was monitored at about 0.191, 0.08, 0.05, 0.04, 0.03 and 0.02 tons / ha / yr for A. confusa, L. formosana, A. montana. P.taiwaniana, F. griffithii and Z formosana_ respectively. Trend of soil loss from six- species plantation decreased with increasing ages. The water loss from the mentioned reforestated areas was measured at 36.2, 22.1, 31.2, 24.2, and 17.3 mm / yr respectively.